Investigation of Professional Identity Formation Processes of Primary Teachers: A Case Study - Çavuş Şahin; Derya Girgin (Anı Publishing, 2019)
The aim of this study is to examine the formation process of the professional identities of primary teachers. The research was designed in the case study design from qualitative research patterns.In this study, a holistic multi-state pattern is used, where multiple situations are present and each situation is handled and compared. The study group consisted of 12 primary teachers (6 females, 6 males) who work in Çanakkale city center and districts in the 2015-2016 academic year. The criterion sampling type, which is one of the purposive sampling types, was used to determine the study group. In order to examine the identity formation processes in the research, various activities were applied. The data obtained in the research were analyzed by content analysis method. According to the results obtained from the research, many themes and sub themes have been identified which point to different structures of professional identity. Finally, the discussion and suggestions for the formation of the professional identity of the primary teachers are presented according to the findings.